HUBUNGAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PRODUKTIF JURUSAN TATA BUSANA SMK NEGERI 1 AMPEK ANGKEK TAHUN AJARAN 2012/2013 - Febriany, Eka; Katin, Yusmar Emmy; Ernawati, Ernawati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
The purpose of the study was to examine the relationship variables with the variable learning discipline learning outcomes, and measure the closeness of the relationship between the two variables. This type of research is descriptive correlational. The population in this study were students of class X and XI majors SMK 1 dressmaking Ampek Angkek totaling 47 individuals and the entire population sampled. As an instrument to determine student learning discipline using a questionnaire (questionnaire) that have been tested for validity and reliability, while learning to know the results obtained in productive subjects of documentation studies teachers. Analysis using Achievement Level Percentage of respondents (TCR), correlation analysis using the Pearson Product Moment Correlation and continued with the t test for the significance of the correlation analysis and to test the hypotheses using correlation coefficient analysis and correlation coefficients analysis of significance. The results showed that, the percentage of respondents' level of achievement on indicators of discipline learned at school by 61% in the low category and the discipline of learning at home indicator score obtained by 63% with the low category, the overall percentage of respondents in the achievement of student learning discipline variables obtained a score of 62% with low category. While the results of productive study subjects most students received grades that are not completed in the amount of 66% and only 34% of students who pass. Correlation analysis was the score of 0.608 with a strong correlation interpretation, correlation significance test showed price t count> t table (21.004> 2.021) which means that the Ha which says there are positive and significant relationship between the discipline of learning to the learning outcomes of students earning subjects Programs SMK 1 dressmaking Ampek Angkek received a significant level of 95%. Â Â Kata kunci: Disiplin, Pelajaran Produktif, Hasil Belajar